1+5x-3x=-11+6x

Simple and best practice solution for 1+5x-3x=-11+6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1+5x-3x=-11+6x equation:


Simplifying
1 + 5x + -3x = -11 + 6x

Combine like terms: 5x + -3x = 2x
1 + 2x = -11 + 6x

Solving
1 + 2x = -11 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
1 + 2x + -6x = -11 + 6x + -6x

Combine like terms: 2x + -6x = -4x
1 + -4x = -11 + 6x + -6x

Combine like terms: 6x + -6x = 0
1 + -4x = -11 + 0
1 + -4x = -11

Add '-1' to each side of the equation.
1 + -1 + -4x = -11 + -1

Combine like terms: 1 + -1 = 0
0 + -4x = -11 + -1
-4x = -11 + -1

Combine like terms: -11 + -1 = -12
-4x = -12

Divide each side by '-4'.
x = 3

Simplifying
x = 3

See similar equations:

| 7.7x-13.3=56 | | 2x+8=5x-3+2x+1+x+6 | | 6x+7y=162 | | 810=27(z+6) | | -4(6x+7)=316 | | 5(y+6)=y+3+2y | | -0.7777(x+3)=14 | | 1/161/2 | | (4+2k)6+3k= | | 3x^2-9600x+100p=0 | | 8x-2-5x+7=2x+4 | | 909=6c+111 | | x^2+6x=952 | | 4z-2=2z+2 | | k/2=lna | | 13x^2+78x+117=0 | | 0.6666(x+13)=22 | | -1-7x-x=-23 | | x+2x=82 | | N+32=67 | | 5k-12=k | | -1+8k=79 | | 0.6667(x+13)=22 | | 5(-7x+2)=270 | | 4+21x=2.50 | | -110+8x=30+x | | 625x^4=1000x^3 | | Z-5=-11 | | -32=6x+4x+8 | | -14=2(w-3)-4w | | 6x+10=6x+94 | | (X+3)(x+6)=189 |

Equations solver categories